A bio-derived char-forming strategy for surface fireproofing: Functionalization of UV-curing flame-retardant coating with vinyl-modified tannic acid. (5th April 2021) - Li, Yue; Qu, Zhencai; Wu, Kun; Lv, Peng; Meng, Huifa; Zheng, Haoting; Shi, Jun; Lu, Mangeng; Huang, Xiaomei
Graphical abstract: Highlights: An UV-curing flame-retardant coating containing tannic acid was successfully prepared. The coated PET matrix can pass the UL-94 V-0 rating easily. Effect of different tannic acid content on flame-retardant properties was studied. The thermal behavior of cured coating was investigated by thermogravimetric analysis. Abstract: In this work, a bio-derived char-forming strategy for surface fireproofing was developed. Specifically, a vinyl-modified tannic acid, (VTA) was synthesized by a ring-opening reaction between tannic acid and glycidyl methacrylate. Integration of epoxy acrylate resin, VTA and tri-(glycidyl methacrylate) phosphate (TGMA), a novel UV-curing coating was prepared, which rendered the PET sheets with superior fireproofing effect. PET samples that were surface coated with the designed UV-curing agent displayed a UL-94 V-0 rating. The peak heat release rate (peak HRR) for combustion of PET was reduced by 10.66% upon application of the flame-retardant coating in cone calorimetry tests. However, the total smoke release (TSR) increased by 48.28% due to pyrolysis of tannic acid produces 1, 2, 3-benzenetriol and carbon dioxide, plus the triol underwent partial combustion with the formation of large amount of particulates. The thermal behavior of cured coating revealed that the presence of high carbon content aromatic tannic acid promoting cationic crosslink and char formation ability. When 40% VTA was added into a coating, the pyrolysis char yield increased by 36.88%. Furthermore, the capability of inhibit heat transfer with the presence of VTA significantly decreased the maximum rate of weight loss for the coating by 85.97%. The increase in the VTA content promoted crosslinking density of the coating, which leads to good rigidity, outstanding abrasion resistance and remarkable water fastness.